Thu hồi đồng từ bản mạch in (PCBs) chất thải điện tử bằng cách hòa tách và điện phân - Hưng, Hà Vĩnh; Mai, Cao Xuân; Hải, Huỳnh Trung; Chí, Trần Đắc; Lee, Jae-chun; Jeong, Jinki; Yoo, Jamin (Vietnam Journal of Chemistry, 2012)
In the present paper, a study on laboratory scale to perform a treatment for valuable metals recovery from printed circuit boards (PCBs) of waste electric and electronic equipment (WEEE) is reported. A leaching process, coupled by electrowinning, is then proposed in order to reduce the volume of the waste material and to recover selectively valuable metals, such as copper. During the leaching step, carried out by using ammonia ammonium chloride solution at room temperature, several factors were investigated (pulp density, time of treatment). The leached liquor has been successfully treated with an electrowinning process, to recover copper. The curent efficiency was of about 93%. The experimental results obtained, showed the technical feasibility of the process.